A study of successful applicants' views of a social work admissions process. (July 2013) - Campbell, Jim; Campbell, Anne; Das, Chaitali
Summary: There are substantial variations in the way that applicants are selected for social work programmes in the UK and across the world. This article begins by reviewing the literature in this field, revealing debates about how effective and reliable are methods of assessment used during admission processes. It then describes a cross-sectional survey of new social work applicants ( n  = 203) to two programme providers, describing demographic characteristics and their experiences of the admissions process. Findings: A number of themes emerged from two sets of findings. There were variations in demographic characteristics, particularly in terms of gender and religion. The study was particularly interested in how students viewed the admissions process. Most students were satisfied with admissions processes, and there were some differences in views about the methods used. The article concludes by describing changes to the admissions system that were partly informed by the study. The article acknowledges the expected bias in the methodology, given that successful applicants were surveyed and not those who were not successful. Applications: The authors discuss the study findings in the context of national and international literature and suggest that more rigorous attention should be paid to such evaluations to enable this important area of education and workforce development to be better understood.